about 8.1
2006-12-11 09:56:25
·
answer #1
·
answered by tmlfan 4
·
1⤊
0⤋
First we would label the shorter leg X. and when you consider that the longer leg is 2cm more effective tahn the shorter leg, we would lable the longer leg X+2. because the hypotenuse is 2cm longer than the longer leg, its length will be equivalent to (X+2)+2 or in reality X+4. then you ought to apply the pythagorean thereom (a squared+bsquared = c squared, the position c is the hypotenuse) to create an equation. So let a=X, let b =X+2, c=X+4 (x)^2+(X+2)^2=(X+4)^2 that's your equation, and one you component out the exponents you get: X^2+X^2+4X+4=X^2+8X+16 now integrate like words: 2X^2+4X+4=X^2+8X+16 next, you want to make the equation equivalent to 0, so that you subtract whats on the right of the equivalent signal. X^2-4X-12=0 you are able to now use the quadratic formula (x=-b+-Sq. root(b^2-4ac)/2a) to locate the fee of x, (a is a million, b is -4, c is -12) AFter fixing with the formula you need to get x to be both 6 or -2 becuase of the plus or minus signal. when you consider that we are coping with triangles, the length of X must be efficient, eliminating -2 as an answer. So X=6. X+2=6+2=8. X+4=6+4=10. you need to get 6 for the shorter area, 8 for the longer area, and 10 for the hypotenuse. i wish that permits!
2016-11-25 20:59:12
·
answer #2
·
answered by ? 4
·
0⤊
0⤋
Let us call the length of the hypotenuse h . Then the length of the other unknown side will be ½h
Thus, h² = 7² + (½h)² = 49 + ¼h²
Therefore, h² - ¼h² = 49
¾h² = 49
h² = 49 x 4 ÷ 3 = 196 ÷ 3
h = square root of (196 ÷ 3)
= 8·0829 (approx. 8·08cm)
2006-12-11 06:00:55
·
answer #3
·
answered by deedsallan 3
·
1⤊
0⤋
let the length of hypotenuse = x
one side = 7 cm.
second side = x/2
we have x^2 = 7^2 + (x/2)^2
x^2 - x^2/4 = 49
3x^2/4 = 49
x^2 = 49*4/3
x = square root of (49 * 4/3)
= 7 * 2 /sq.root 3
x = 8.08 cm. Ans.
2006-12-11 06:04:45
·
answer #4
·
answered by ATS 2
·
1⤊
0⤋
Guess the second leg is x. Then the hypotenuse = 2x.
Now Pythagoras: 7^2 + x^2 = (2x)^2
Or: 49 = 3x^2. So x^2 = 49/3 and x = 7/root(3)
(The negative possibility you can forget here).
The hypotenuse = 2 * 7/root(3) = 8.08...
Th
2006-12-11 06:13:27
·
answer #5
·
answered by Thermo 6
·
1⤊
0⤋
You know this is a 30-60-90 triangle because one leg is half the hypotenuse. In these triangles, you divide the longer leg by sqrt(3) to get the shorter leg. The shorter leg in this case is 7/sqrt(3) = 7sqrt(3)/3, so the hypotenuse is 14sqrt(3)/3.
2006-12-11 05:47:41
·
answer #6
·
answered by Anonymous
·
1⤊
0⤋
H= SQ Root of 65.31
H Squared= (7 squared) + (H/2 Squared)
Solve for H
H= Square Root of 49 times 4/3
2006-12-11 05:51:17
·
answer #7
·
answered by bill5x 1
·
2⤊
0⤋
Let's call the hypoteneus 'h'.
By the pythagorean Theorem:
7^2 + (1/2 h)^2 = h^2.
With a little algebra, we have:
49 + 1/4 h^2 = h^2,
49 = 3/4 h^2,
196/3 = h^2,
h = 14/(square_root(3)).
I hope this is clear enough.
2006-12-11 05:47:35
·
answer #8
·
answered by Bugmän 4
·
0⤊
1⤋
Use the equation a^2 + b^2 = c^2 where c is the hypotenuse.
7^2 +(0.5c)^2 = c^2
49 + 0.25c^2 = c^2
49 = 0.75c^2
65.33 = c^2
c=8.08 cm
2006-12-11 05:47:22
·
answer #9
·
answered by chris_in_columbia 2
·
0⤊
2⤋
You apply Pitagorean equation:
x² + y² = h²
x=7 cm
y = 0.5 h
h = ?
2) Substitute the given values:
7² + 0.5h² = h²
Solve for h:
7² =h²-0.5h²
0.5h² = 7²
h² = 7²/0.5
h² = 98 cm²
h = 9.89 cm (just take the positive value of the square root)
That's it!
Good luck!
2006-12-11 05:49:37
·
answer #10
·
answered by CHESSLARUS 7
·
0⤊
2⤋
Hey...all you have to do is translate this to an equation. Use a^2+b^2=c^2. a = 7, b=.5h, and c=h. Solve for h.
2006-12-11 05:47:57
·
answer #11
·
answered by jrgreenfield1 2
·
0⤊
1⤋